2022
DOI: 10.1111/spol.12849
|View full text |Cite
|
Sign up to set email alerts
|

Social security or insecurity? The experience of welfare participation by financially vulnerable households in the Netherlands

Abstract: Social welfare aims to support financially vulnerable households by protecting them from financial shocks and providing them with a basic standard of living. Many eligible households, however, do not take up social welfare. We present the results of in-depth interviews with 31 members of financially vulnerable households in two large Dutch cities about their experiences with welfare. We examined the role that money played in their lives, what inhibited them from taking up social welfare, and how they sought su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 61 publications
(127 reference statements)
0
4
0
Order By: Relevance
“…There are some discussions on uncertainty in the scholarship on administrative burdens. This literature has examined how citizens experience their interactions with the state (Barnes & Petry, 2021;Nisar, 2017;Simonse et al, 2023), the strategies, and behaviors of citizens in the bureaucratic encounter (Bisgaard, 2020;Nielsen et al, 2020;Nisar, 2018) as well as differences and inequalities in the citizens possibilities to navigate the encounter (Christensen et al, 2020;Chudnovsky & Peeters, 2021;Döring, 2021;Masood & Azfar Nisar, 2020;Olsen, 2022;Simonse et al, 2023). Moreover, scholars have looked into the consequences of administrative burdens in terms of how the experience of burdens may lead to a decline in take-up (Brodkin & Majmundar, 2010;Fox et al, 2020;Heinrich, 2016) as well as how administrative burdens can be reduced Linos et al, 2020).…”
Section: What Do We Know About Uncertainty In Citizen-state Interacti...mentioning
confidence: 99%
“…There are some discussions on uncertainty in the scholarship on administrative burdens. This literature has examined how citizens experience their interactions with the state (Barnes & Petry, 2021;Nisar, 2017;Simonse et al, 2023), the strategies, and behaviors of citizens in the bureaucratic encounter (Bisgaard, 2020;Nielsen et al, 2020;Nisar, 2018) as well as differences and inequalities in the citizens possibilities to navigate the encounter (Christensen et al, 2020;Chudnovsky & Peeters, 2021;Döring, 2021;Masood & Azfar Nisar, 2020;Olsen, 2022;Simonse et al, 2023). Moreover, scholars have looked into the consequences of administrative burdens in terms of how the experience of burdens may lead to a decline in take-up (Brodkin & Majmundar, 2010;Fox et al, 2020;Heinrich, 2016) as well as how administrative burdens can be reduced Linos et al, 2020).…”
Section: What Do We Know About Uncertainty In Citizen-state Interacti...mentioning
confidence: 99%
“…Financial stress is the subjective feeling of having too few financial resources. The experience of financial stress occurs when pressing financial concerns are appraised as exceeding available resources that, in turn, evoke worry, rumination and a short-term focus (Van Dijk et al, 2022). Financial stress is associated with different aspects of one's objective economic situation, such as having a low income, debts and the absence of savings (Drentea and Reynolds, 2015;Johar et al, 2015;Ruberton et al, 2016).…”
Section: Capability Factorsmentioning
confidence: 99%
“…There is some evidence that benefits recipients may fear sanctions due to unjustly received benefits (Reeves and Loopstra, 2017; Wright et al, 2020). In a qualitative study among low-income households in the Netherlands, Simonse et al (2022) found that the fear of reclaims was the main reason respondents refrained from welfare participation. Bhargava and Manoli (2015) found that attempts to reduce fear of audits had little effect.…”
Section: Introductionmentioning
confidence: 99%
“…Government support and interventions may be insufficient to improve financial wellbeing. Shame, stigma, and distrust can act as barriers to the uptake of financial help (Simonse et al, 2023). Understanding how to overcome these barriers is key to improving the financial well-being and thus provides an important yet challenging direction for future research.…”
Section: Directions For Future Researchmentioning
confidence: 99%